Frequency domain homogenization for the viscoelastic properties of spatially correlated quasi-periodic lattices. (January 2019) - Mukhopadhyay, T.; Adhikari, S.; Batou, A.
Highlights: Irregular lattices are analysed considering the compound effect of viscoelasticity and stochasticity. A practically relevant stochastic modelling approach is developed in conjunction with quasi-periodic lattices to consider spatially correlated structural and material attributes. Computationally efficient and physically insightful closed-form analytical formulae are developed for analysing viscoelastic properties of spatially irregular lattices in frequency domain. Graphical abstract: Abstract: An analytical framework is developed for investigating the effect of viscoelasticity on irregular hexagonal lattices. At room temperature many polymers are found to be near their glass temperature. Elastic moduli of honeycombs made of such materials are not constant, but changes in the time or frequency domain. Thus consideration of viscoelastic properties are essential for such honeycombs. Irregularity in lattice structures being inevitable from practical point of view, analysis of the compound effect considering both irregularity and viscoelasticity is crucial for such structural forms. On the basis of a mechanics based bottom-up approach, computationally efficient closed-form formulae are derived in frequency domain. The spatially correlated structural and material attributes are obtained based on Karhunen–Loève expansion, which is integrated with the developed analytical approach to quantify the viscoelastic effect for irregular lattices. Consideration of such spatially correlated behaviour can simulate the practical stochastic system more closely. The two effective complex Young's moduli and shear modulus are found to be dependent on the viscoelastic parameters, while the two in-plane effective Poisson's ratios are found to be independent of viscoelastic parameters and frequency. Results are presented in both deterministic and stochastic regime, wherein it is observed that the amplitude of Young's moduli and shear modulus are significantly amplified in the frequency domain. The response bounds are quantified considering two different forms of irregularity, randomly inhomogeneous irregularity and randomly homogeneous irregularity. The computationally efficient analytical approach presented in this study can be quite attractive for practical purposes to analyse and design lattices with predominantly viscoelastic behaviour along with consideration of structural and material irregularity.